Digital experience and citizen participation in bridging ethnic divide: an analysis of young generation in Malaysia - Samsudin A. Rahim (Penerbit Universiti Kebangsaan Malaysia, 2018)
Information and communication technologies provide communities, service providers and advocates with mechanisms through which service can be more effectively and efficiently provided to the young generation. The young generation and these technologies can unite to create an agenda for positive change that will ultimately benefit them and society. The role that information and communication technologies may play and the impact they may have on the ethnic divide and national unity among the young generation in a multicultural society are not well understood, and there are gaps in the evidence base surrounding the possibilities and approaches for national integration that involves information technologies. This paper investigates the usage of ethnic media and issues related to the ethnic divide in multicultural Malaysian society. More specifically, internet use, types of participation, ethnic identity and their interrelations were observed. A national sample of 1,640 respondents between the ages of 21 and 40 years were interviewed. The results indicated that those with more experience and longer usage of the Internet showed higher levels of online and offline participation. The high penetration of information and communication technology among the young generation provides an opportunity for active citizen participation that could lead to a better understanding of the citizens’ rights and responsibilities, which can form the basis for bridging the ethnic divide.